Nível de ansiedade e comportamento alimentar em pacientes com doença celíaca - FERREIRA, Juliana Oliveira (2023)
Celiac disease is a chronic disease that occurs in the small intestine, its treatment is based on diet, through the permanent exclusion of gluten. However, following a gluten-free diet imposes adaptations and restrictions to daily life and psychosocial impacts. Thus, although the gluten-free diet is physically beneficial for the individual, its restrictive nature can affect relationships with food and result in disordered eating behaviors. Objective: to verify the association between anxiety level and disordered eating behaviors in celiac patients. Methodology: This is a cross-sectional study carried out with adults diagnosed with celiac disease of both sexes and aged between 15 and 70 years. Data were collected through an online form composed of: Free and Informed Consent Form, social, economic, demographic aspects, anthropometric data and aspects of celiac disease, State-Trait Anxiety Inventory (STAI) and a behavioral assessment questionnaire. to feed. Descriptive statistics of the variables and multiple binary logistic regression analysis were performed with alpha at 5%. Results: Of the total sample (n=96) research participants, 96.88% were female, 35.42% were between 30 and 39 years old, 29.17% lived in the Midwest region, 53.13 % have a postgraduate degree, 53.13% have a family income of more than 4 minimum wages, 56.25% are eutrophic and 96.88% responded that they strictly follow a gluten-free diet. As for the level of anxiety, 48.96% of those studied had an average level of anxiety. More than 90% of celiacs did not show uncontrolled eating and did not transgress the gluten-free diet, however 43.75% restricted food and 39.58% had emotional eating. A significant association was found between anxiety level and emotional eating (p=0,0001). Conclusion: Therefore, the importance of research that evaluates emotional factors and how they interfere in the eating behavior of people with celiac disease is emphasized, so that specific interventions can be designed for this population in order to contribute to the quality of life of these patients.